Harmonization and Good Relations in Polygamous Families - Ely Lidiana (UNISSULA Semarang, 2021)
This research is made based on facts and circumstances that occur, which is a daily picture of women who live as wives in a polygamous marriage. In this paper, an argument will be presented that will refute the negative opinion of some people about polygamous marriage, where for most people, especially feminists who have the opinion that polygamous marriage is only aimed at venting sexuality and more discriminating against women and children. In proving this argument, the author uses descriptive qualitative research methods with a phenomenological approach where data collection is done by direct observation, interviews and documentation. This research was conducted in a village which is the village where the author was born and is the author's family.